Geochronology and geochemistry of the Neoproterozoic–Mesozoic intrusive rocks in the Xinlin area, northeastern China: new constraints on the tectonic evolution of the Erguna block - Lu, Sheng; Li, Chenglu; Alam, Masroor; Song, Zhichao; Zhu, Xiannan; Fu, Anzong; Yang, Wenpeng (Frontiers in Earth Science, 2025)
The occurrence of intrusive rocks within the Xinlin area, northeastern China, provides insights into the Neoproterozoic–Mesozoic geodynamic setting of the Erguna block. In this study, we present petrographic, geochemical, and geochronological data on intrusive rocks from the Xinlin area. Zircon U–Pb and muscovite 40Ar/39Ar geochronology reveal that magmatism occurred during the Neoproterozoic (ca. 864.98 Ma), Early Ordovician (ca. 470.0 Ma), Late Carboniferous (ca. 306.9 Ma), Early Permian (ca. 296.9 Ma), and Early Cretaceous (ca. 117.8 Ma) periods. The Neoproterozoic and Early Ordovician intermediate–mafic intrusive rocks have low Rb/Sr contents, high Mg#, and weakly negative Eu anomalies. These results suggest that the magma sources of these rocks varied: intermediate–acidic magmas were derived from the lower crust, and intermediate–mafic magmas originated from the mantle and were subsequently contaminated by crustal material. In contrast, the Late Carboniferous, Early Permian, Late Triassic–Early Jurassic, and Early Cretaceous intermediate–acidic intrusive rocks display high Rb/Sr contents, low Mg#, and strongly negative Eu anomalies, indicating derivation from the partial melting of the lower crust. Our findings, along with previous studies, suggest that Neoproterozoic intrusive rocks were formed during the breakup of the Rodinia supercontinent. The Paleozoic intrusive rocks are associated with the collision and amalgamation of the Erguna and Xing’an blocks, as well as the Songnen and Xing’an blocks. Early Mesozoic intrusive rocks were developed during the subduction of the Mongol-Okhotsk oceanic intracontinental system. Finally, the late Mesozoic intrusive rocks were formed in a non-orogenic extensional setting, potentially linked to the final closure of the Mongol-Okhotsk Ocean or the rollback of the Paleo-Pacific Plate.